TIGIT affects CAR NK-cell effector function in the solid tumor microenvironment by modulating immune synapse strength - Navin, Ishwar; Dysthe, Matthew; Menon, Prashant S.; Baumgartner, Corrine; Sauer, Tim; Varadarajan, Navin; Parihar, Robin (Cancer immunology research, 2025)
Therapies using NK cells that express chimeric antigen receptors (CAR-NK) have been successfully employed against hematologic malignancies. However, solid tumors resist CAR-NKs partly by enriching tumor microenvironments with ligands for NK cell inhibitory receptors. Although the NK inhibitory receptor T-cell immunoreceptor with immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domain (TIGIT) has been implicated in impaired antitumor activity of endogenous NK cells, the consequences of TIGIT expression on engineered CAR-NKs have not been explored. To address this gap, we compared TIGIT-expressing and TIGIT-deleted human CAR-NKs targeting the GD2 solid tumor antigen in tumor immune microenvironment co-cultures and in vivo tumor immune microenvironment xenografts designed to mimic the immunosuppressive environment of solid tumors. TIGIT-deleted GD2.CAR-NKs exhibited antitumor activity, expanded, and persisted within TIGIT ligand-enriched solid tumor environments, whereas TIGIT-expressing CAR-NKs did not. Mechanistic experiments revealed that the improved tumor control resulting from TIGIT loss on CAR-NKs was not dependent on DNAM-1 activation or enhanced cytotoxic potential but rather on downregulation of cell adhesion molecules, weakened cell avidity, and reduced synapse contact duration that, in concert, improved serial killing and allowed more efficient tumor destruction. Our study highlights a noncanonical role for TIGIT in modulating CAR-NK activity that may guide strategies to overcome inhibitory NK receptors like TIGIT and improve the efficacy of CAR-NKs against solid tumors.
Gesehen am 30.01.2026